THE AWARENESS OF HEALTHY INDIVIDUALS ABOUT ATTRIBUTABLE RISK FACTORS OF CANCER - Keser, Ilke; ozdemir, Kadirhan; Berguz, Hilal Utkan; Uysal, Songul Atasavun; Suner-Keklik, Sinem; Yentur, Songuel Baglan; Aras, Mukaddes (Dokuz Eylul Univ Inst Health Sciences, 2023)
Purpose: This study aimed to determine the awareness of healthy individuals about the attributable risk factors of cancer and investigate the consistency of their ideas.Material and Methods: A review of relevant literature was undertaken to assemble a list of possible causes of cancer. Seventy-six healthy individuals were interviewed. Individuals were asked to declare their opinion by scoring the potential 15 cancer risk factors between 0-4. One week later, the opinions were retaken to evaluate intra-rater reliability.Results: Individuals mostly agreed with the attributable risk factors including nuclear accident (96.0%), smoking (94.8%), stress (93.5%), having a family history of cancer (92.1%), alcohol (90.8%), air pollution (86.8%), plastic (84.2%), mobile phone use (79.0%), washing agents (77.7%), sunlight exposure (69.77%), occupational exposure (67.1%), being overweight (63.1%), infection (57.9%), fatigue (54.0%), except age (34.2%). All risk factors had significant intra-rater consistencies in different levels (fair to perfect) between the two-time points (p<0.05).Conclusion: It was determined that 14 out of the 15 risk factors carried a cancer risk according to the individuals. The formation of sufficient awareness and acceptance of risk factors has revealed the necessity of raising awareness in the fight against cancer.
Keywords: Awareness; cancer; public health; risk